Problematyka małych regionów w polityce spójności Unii Europejskiej - Pancer-Cybulska, Ewa (Small Regions as the Subject in the EU Cohesion Policy, 2006)
There exist problems with accessing small regions to the common regional policy. Small regions are defined on the NUTS 3 level, but they also exist as NUTS 2 and NUTS 1 regions. The consequences of the successive EU enlargements change the common regional policy. It means selection criteria, objectives, financial frames and expenditure on regional policy change.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 392-402